La Bolsa de Valores de Colombia. Su historia y relación con la Universidad EAFIT (2019)
The Colombian Securities Exchange Market has undergone through many stages and has been handled by diverse institutions, which have born and disappeared over the years according to the changing environment. A century passed since the creation of the first stock market in the country until the Bolsa de Valores de Colombia was born as a result of the unification of the Colombian Securities Exchange Markets. A century of history that is described in a detailed form. For the development of Capital Markets in Colombia and its Securities Exchange Market, the support of academics has been crucial, and EAFIT University has been a fundamental actor in this process.